Studi Perancangan Identitas Visual Wilayah Karimunjawa - Arif Priyono Susilo Ahmad (Bina Nusantara University, 2013)
Effective communication is a critical need in our lives. Communication that is not running properly will impede the flow and the system of social activity. Living in a world filled with information needs language as a right marker so that the meaning of a message can be conveyed properly. At such moments, a marker, which also functions as the identity for the people, demands to look unique, creative, communicative, and comprehensible globally, beyond the boundaries of culture and geography. Visual markers of an area are needed so that miscommunication can be reduced. Visual markers were developed in regard to communication strategies within the context of destination branding. Sharp communication strategy would manifest in the form of creative concept, a kind of platform on which to base and the main idea behind the overall design visualization. Manifestation the visual form of logo design, typography, tone color, shapes, graphic elements, mascot, pictograms, wayfinding, posters, merchandise, and so on. The visual identity of the region, in relation to destination branding program, specifically intended for a destination region, will raise the values of locality, the uniqueness, diversity, and distinctiveness of the region. Designing visual identity Karimunjawa region in this case study apply the principles of creativity and uniqueness that is processed into a visual appealing, distinctive, and attractive, yet understated and powerful in raising local elements.